The theoantropocentric based model of demand and supply - Pawenang, Supawi; Supriyati, Sri; Kartika, Betania; A. Yani, Burhanudin (2019)
This paper is focus to criticize Marshall's supply and demand theory. Marshall’s theory was indentified by strengthness and weakness, so be looked up solution to make a perfect theory. The result of analysis describe that Marshall's theory is a basic of most theory in study of economics. Many theory, like a monetary theory, fiscal theory, consumer behavior theory, etc., was developed from that theory. On the other hand, Marshall's theory has some weaknesses if looked up from morality or religious perspective, because morality and religious value absent from theory. So, some weaknesses of theory be repaired by inserting axis and ordinate reflector, that can be used to controlling outcome transaction from morality and religios value perspective. The new supply and demand theory is named universal-ethics supply and demand theory.